On the optimal labor income share - Jakub Growiec; Peter McAdam; Jakub Mućk (European Central Bank (ECB), 2018)
Labor's share of income has attracted interest in recent years reflecting its apparent decline. These falls, witnessed across many countries, are usually deemed undesirable. Any such assertion, however, begs the question of what is the socially optimal labor share. We address this question using a micro-founded endogenous growth model calibrated on US data. We find that in our central calibration the socially optimal labor share is 17% (11 pp) above the decentralized equilibrium, calibrated to match the average observed in history. We also study the dependence of both long-run growth equilibria on model parameters and relate our results to Piketty's "laws of Capitalism". Finally, we demonstrate that cyclical movements in factor income shares are socially optimal and that the decentralized equilibrium typically does not generate excess volatility.
Keywords: O33; O41; 330; Labor income share; Endogenous growth; Factor augmenting endogenous technical change; Social optimum; Decentralized allocation; Lohnquote; Allokation; Endogenes Wachstumsmodell; USA